Is the conception of decent work susceptible to decolonial appropriation? Reflections from the criticism of the modern concept of development - Beltramelli Neto, Silvio (2021)
Guided by an abridgement of the theory of historical process of construction and critique of the modern concept of development, as disseminated in the field of international cooperation, the article aims to reflect on how the assumptions of critical post-developmental and decolonial thinking can be applied to the work of the International Labor Organization, especially with regard to the promotion of Decent Work – a concept based on theory and aspirations markedly associated with the current notion of sustainable development – to then respond to the following research problem: is the conception of Decent Work susceptible to decolonial appropriation? The affirmative answer results from an applied theoretical exploratory study, that led us to draw propositional notes on the issue, through the methodological approach of qualitative bibliographic analysis.